Nuclear Deterrence and National Security in the Twenty First Century - Ms. Amna Saqib; Mr. Samran Ali (CISS Insight Journal, 2023)
Using nuclear weapons has been a subject of intense debate in international affairs, eliciting ethical, political, and security concerns. Among these concerns, security is the primary motivation driving states to pursue nuclear capabilities. This research paper explores the concept of the structural realist theory of international relations to examine the significance of nuclear weapons in ensuring the survival of a state. According to this theory, possessing nuclear capabilities is a potent deterrent against potential adversaries. This study critically evaluates the credibility of nuclear deterrence in the present-day context, considering various factors such as technological advancements, the proliferation of nuclear weapons, and emerging security challenges. Furthermore, it investigates the intricate dynamics of regional nuclear rivalries and their consequential impact on national security calculations. The research uses case studies of North Korea and Ukraine, analyzes the facets of their nuclear programs, and sheds light on the complexities associated with nuclear proliferation. This paper aims to contribute to the ongoing discourse on nuclear weapons policy, global security, and arms control in the twenty-first century by critically examining the advantages, risks, and challenges associated with nuclear deterrence.